2016
DOI: 10.18203/2320-1770.ijrcog20163432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of maternal anemia in tertiary care centre and its neonatal outcomes

Abstract: Background: Anaemia is the leading cause of maternal mortality and morbidity in India. According to WHO globally, anaemia affects 1.62 billion people. In India, National Family Health Survey 2009, reports that 55% of women in reproductive age group are anaemic. Maternal anaemia can cause many perinatal complications like low birth weight, preterm delivery, low APGAR score, suboptimal infant breast feeding behavior. Methods: This prospective study was conducted in Department of OBG at VIMS and RC for a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Among anemic mothers, the risk of perinatal mortality was high, which was similar to the study conducted by Nair et al [15] and Lone et al [16] The study showed a significant association between maternal anemia and perinatal mortality, which was already established in many studies. Nair et al [17] and Sangeeta and Pushpalatha [18] also showed that the risk of IUGR was more in anemic mothers and the findings are similar to our study. Borah and Agarwalla, [19] showed that LBW baby was 1.93 times more among anemic mothers, which are similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Among anemic mothers, the risk of perinatal mortality was high, which was similar to the study conducted by Nair et al [15] and Lone et al [16] The study showed a significant association between maternal anemia and perinatal mortality, which was already established in many studies. Nair et al [17] and Sangeeta and Pushpalatha [18] also showed that the risk of IUGR was more in anemic mothers and the findings are similar to our study. Borah and Agarwalla, [19] showed that LBW baby was 1.93 times more among anemic mothers, which are similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 92%